Anatomy of a Cyberattack: Part 2: Managing a Clinical Pathology Laboratory During 25 Days of Downtime. Issue 5 (21st February 2022) - Goodwin, Andrew; Wilburn, Clayton; Wojewoda, Christina; Mesec, Jessica; Cacciatore, Lori S; Grove, Staci-Anne; Hajder, Armina; Stowman, Anne M
Abstract: Objectives: Our academic health care institution was the victim of a cyberattack that led to a complete shutdown of major patient care, operational, and communication systems, including our electronic health record (EHR), laboratory information system, pharmacy, scheduling, billing and coding, imaging software, internet, hospital shared computer drives, payroll, and digital communications. The EHR remained down for 25 days, significantly affecting our clinical pathology (CP) laboratory operations. Methods: During the downtime, our CP laboratory incorporated manual interventions for patient specimen testing, recruited additional staff for reporting results, and employed multiple communication modalities to support patient care. The crisis required a swift response, employing innovative approaches to mitigate patient harm; regular, multidisciplinary engagement; and consistent, broad-reaching communications. CP leadership worked with hospital administration, staff, and our referral clients to provide the timely laboratory results needed for acute patient care. Results: During this downtime, the laboratory lacked accurate information about the number of patient samples diverted to other laboratories, the number of specimens processed, and the number of test results reported. Conclusions: This paper focuses on the approaches the CP division took to develop and maintain downtime operations. Laboratories should consider these strategies in preparation for a prolonged downtime.